Paparan Subletal Mikroplastik Polistirena pada Media Pemeliharaan Menurunkan Pertumbuhan dan Efisiensi Pemanfaatan Pakan Udang Vaname (Litopenaeus vannamei) - Bagus Dwi Hari Setyono; Nurbaiti Saptatriani; Laily Fitriani Mulyani (Jurnal Akuakultur Rawa Indonesia, 2026)
Microplastic contamination is increasingly relevant in shrimp farming because plastic particles may originate from water, feed, equipment, packaging, and polystyrene-based foam materials commonly used throughout aquaculture supply chains. This study evaluated the effects of sublethal exposure to polystyrene microplastics (PS-MPs) in the rearing medium on growth performance and feed utilization efficiency of whiteleg shrimp (Litopenaeus vannamei). A completely randomized design was applied using four nominal concentrations of PS-MPs (0, 10, 20, and 30 mg/L), each with three replicates. PL-30 shrimp were reared for 45 days at a density of 20 individuals per 20-L container. The assessed parameters were absolute length growth, absolute weight growth, specific length growth rate, specific weight growth rate, feed conversion ratio (FCR), and feed utilization efficiency (EPP). Analysis of variance showed that all production parameters were significantly affected by treatment (p<0.001). The control consistently produced the highest values for growth-related traits and EPP, whereas the lowest values were generally observed at 30 mg/L. In contrast, FCR increased markedly in all exposed groups relative to the control. From the control to 30 mg/L, absolute length declined by 31.8%, absolute weight by 53.4%, specific weight growth by 54.0%, and EPP by 65.4%, while FCR increased by 141.4%. These findings indicate that PS microplastics in the culture medium are strongly associated with reduced production performance of whiteleg shrimp, especially through poorer growth and less efficient feed utilization.